The immunomodulatingaction of lipid-lowering drugs - de Moura, Pereira (2023)
Atherosclerosis is the principal cause of death in developed countries. Integral to the process there seems to be a reaction of the vessel to an aggression, be it physical, chemical, infectious or immunologic. Whatever the factor responsible for the aggression, inflammatory and immune responses exert a primordial role in the ampli.ication and maintenance of the atherogenic process. Of allthe known risk factors, a raised serum cholesterol, particularly the LDL fraction, is one of the most important. Certain authors believe that many of the other risk factors only become important in the presence of hypercholesterolaemia. Therefore, pharmacological agents which Jower cholesterol have a central role in the prevention and treatment of cardiovascular disease, as has been proved in a number of clinicai, primary and secondary, prevention triais. Apart from their effect on lipid levels, the different lipid-lowering drugs, particularly the statins and the fibrates, have a number of actions on inflammatory and immune mechanisms, which, while not completely understood, are of great therapeutic interest. This article presents a revision of the anti inflamma tory and immunologic actions of the different lipid-lowering drugs, particularly the statins, the fibrates and probucol.